Representasi Resistensi Anak Muda Dalam Konten #KaburAjaDulu oleh Influencer Gerald Vincent - Khairani, Najmi Rizki; Wulandari , Irawati Sri (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2025)
This study analyzes the representation of the #KaburAjaDulu (Running Away From Indonesia) in three social media posts produced by influencer Gerald Vincent (@geraldvincentt) on Instagram and TikTok. The hashtag, which first appeared in 2023 and went viral, depicts the current state of the country. The approach used in this study is qualitative. This research attempts to describe the #KaburAjaDulu content phenomenon from the perspective of Stuart Hall's representation of ideas. This research reveals how the narrative of "running away" from Indonesia is interpreted as a critique of the nation's social, political, and economic conditions. The analysis shows that Gerald's content frames this narrative in an educational and populist manner, voicing young people's frustration with a system perceived as unfair. Issues such as foreign responses, bureaucratic regulations, and freedom of expression on social media further reinforce the public discourse surrounding the intellectual exodus. This study highlights the crucial role of social media in destabilizing political discourse and the identity of the younger generation amidst declining trust in state institutions.